Filogenia e classificação de Megachile Latreille, 1802 grupo Pseudocentron, sensu Mitchell, 1980 - Igor Rismo Coelho (2016)
Megachile Latreille is the most diverse genus of Megachilidae bees, with more than 1100 species and 58 subgenera currently recognized; it is found in a wide diversity of habitats through the world. The genus is taxonomically poorly known and its phylogenetic relationships are barely understood. Most subgenera have not been revised and many species still needs a correct association to the valid subgenera. The Pseudocentron generic group was recognized by Mitchell (1980) and it has been supported by many authors as a natural group, although no phylogenetic studies have been carried out so far. In the first chapter of this thesis, with the aim of investigate the phylogenetic relationships of this group of subgenera, a matriz was built with 74 terminals and 208 characters of external morphology of males and females, including the male genitalia and associated sternites. The characters were analysed using equal and implied weighting with the software TNT. The results suggest the monophyly of the Pseudocentron group, with the clade consisting of Leptorachis and Acentron appearing as sister group of the remaining subgenera. Moureapis appears as sister group of the clade consisting of (Melanosarus e Pseudocentron clade 1) + Pseudocentron clade 2. Here, we suggest the synonymization of Acentron with Leptorachis; the confirmation of the synonymy, proposed by Michener (2000), of Leptorachina, also with Leptorachis; and the validation of the subgenera Moureapis and Melanosarus. The results also suggest that Pseudocentron subgenus should be recognized as two distinct subgenera (treated here as Pseudocentron clade 1 and clade 2, respectively). New combinations were proposed as follows: M. (Cressoniella) costaricesis Friese and M. (Pseudocentron) manaosensis Schrottky. The second chapter presents the review of the species of Pseudocentron subgenus that occurs in southeastern Brazil. We validated 12 species and described three new: M. (P.) riodocesis, M. (P.) cosvera and M. (P.) ceciliae. New synonyms were suggested: M. perita Mitchell, 1930 e M. delectus Mitchell, 1930 are junior synonyms of M. botucatuna Schrottky, 1913. M. timida Mitchell, 1930 is junior synonym of M. rubricata Smith, 1853. We propose an identification key to the 15 speciess occurring in southeastern region. In the last chapter, we performed a compilation of the gyandromorphism cases documented in the literature for Megachile (Pseudocentron) species. In this study, we described the first case for M. (P.) rubricata, the third for the subgenus. The ginandromorph shows a mosaic pattern of male and female characteristics, the most commom in Megachile bees.